Pleural Fluid Adenosine Deaminase (ADA) Level in Tuberculous Pleurisy - Paudel, YP; Kasyap, AK; Dongol, Y; Shrestha, RK; Aryal, B; Kafle, D (Journal of Chitwan Medical College, 2013)
Adenosine Deaminase (ADA) is used as a well established biological marker for diagnosis of tuberculous pleuritis. The aim of this study was to assess the sensitivity and specificity of ADA in patients with pleural effusion admitted in the medical ward. This was an cross sectional study. The information was gathered only from those patients whose pleural fluid sample was sent for ADA in clinical biochemistry laboratory of KIST Medical College and Teaching hospital. The data was acquired from the medical records of patients attending medical ward. The patients were considered as TB positive if they were clinically diagnosed so and taken as negative otherwise. Fifty six pleuritis patients were evaluated. Using the cut off value of 30 U/L, the overall sensitivity and specificity was 93.3% and 57.1% respectively. The association between ADA findings and the clinical findings were statistically significant (p <0.001). The positive predictive value (PVP) and the negative predictive value (PVN) were 82.3% and 80% respectively. ADA is an inexpensive, rapid and simple test for analysis of tuberculous pleuritis. Though, it is a sensitive test for tuberculosis, due to its low specificity, sometimes negative cases can be considered as positive. DOI: http://dx.doi.org/10.3126/jcmc.v3i3.8634 Journal of Chitwan Medical College 2013; 3(3): 26-27